Ethnographic Regions of Lithuania and the City: Creating of Cultural Integrity - Teleišė, Aušra (Acta humanitarica academiae Saulensis, 2019)
Considering that many papers of urban anthropology written by Lithuanian anthropologists and ethnologists are related to the rural culture, this article raises the question what kind of the relation could be revealed between the city and the ethnographic region. The paper aims to conceptually reveal why a city could or could not be considered as a part of a certain ethnographic region and absolutely represent the identity of an ethnographic region in which it is located. This paper is based on theoretical papers of urban anthropology and sociology, texts by foreign and Lithuanian anthropologists analyzing the concept of a region, papers by Lithuanian ethnologists revealing the features of constructing ethnographic regions of Lithuania; by analyzing the ethnographic and dialect maps of Lithuania. The article proposes that there is no conceptual anthropological definition of a region, however, because region could be constructed externally, it often gains an instrumental and classification function, i.e, to combine or separate smaller units. Specifically, the strict line defining the borders of a region on the ethnographic map marks similarities and differences. The ethnographic regions of Lithuania have been constructed by using the approach which is based on moving from the center (certain features are expressed the brightest) towards the periphery where expression of certain features diminishes. This means that the entire evenly marked area on the ethnographic map is considered as culturally integral. Nevertheless, the ethnographic regions of Lithuania have been formed not only based on ethnographic material, but also based on the historical findings, which legitimizes existence of a certain territory by confirming the origin of the name and formation of borders, also prevalence of dialects, which is considered as one of the most significant identity features of a region. The article highlights that an ethnographic region is perceived not only as a cultural integrity, but it also gains an administrative function along with distinguished organizational centers – cities, approved coats of arms, flags, and established “government”. The article reveals that, in terms of the social structure, a city is a completely different organization in comparison to a rural community representing regional culture. Unlike a rural, which is associated with similarity, closeness, tradition, and stability, a city is defined as a densely populated territory with prevailing variety of people, cultures and activities, individuality, characteristic of continuous development and modernization, whereas closeness stems from the need to survive. The article concludes that belonging of a city to an ethnographic region is questionable because the social and cultural features of the city are different from those associated with an ethnographic region, as constructed cultural integrity, however, a city may be considered as the administrative center of an ethnographic region.